KEPERCAYAAN, KOMITMEN, KOMUNIKASI, PENANGANAN KONFLIK, DAN PERANNNYA TERHADAP KEPUASAN TERHADAP LOYALITAS NASABAH BANK BCA DI SURABAYA - Yunita Arum Safitri (STIE Perbanas Surabaya, 2011)
The purpose of this study was to explore the relationship between trust, commitment, communication, handling conflict, and satisfaction towards the loyalty of customers of Bank BCA. In creating a customer loyalty, trust, commitment, communication, conflict handling and satisfaction are variables to consider in long-term survival for a company, especially in banking industries. It provides the results those only the variables of conflict handling and satisfaction that have a significant positive effect on the customer loyalty variables. This study analyzes to what degree trust, commitment, communication; conflict handling and satisfaction affect the customer loyalty BCA bank in Surabaya. The results of this study showed that the regression coefficient between the variables of the conflict on the handling of customer loyalty is at 0.183 with a t-count of 2.220, while the regression coefficient between the variable satisfaction with the loyalty of 0.302 to 2.883 for t-count test is carried out through a questionnaire with judgment method of sampling of 125 respondents, while the test equipment used in this study is by using SPSS 12.0.